Ultra-thin g-C3N4/MFM-300(Fe) heterojunctions for photocatalytic aerobic oxidation of benzylic carbon centers. Issue 15 (5th July 2021) - Liu, Chengcheng; Luo, Tian; Sheveleva, Alena M.; Han, Xue; Kang, Xinchen; Sapchenko, Sergei; Tuna, Floriana; McInnes, Eric J. L.; Han, Buxing; Yang, Sihai; Schröder, Martin
Abstract : In situ growth of the MFM-300(Fe) on an ultra-thin sheet of graphitic carbon nitride, formed by exfoliation using supercritical CO2, is reported. The resultant composite CNNS/MFM-300(Fe) shows excellent performance in photocatalytic aerobic oxidation of benzylic C–H groups. Abstract : In situ growth of the metal–organic framework material MFM-300(Fe) on an ultra-thin sheet of graphitic carbon nitride (g-C3 N4 ) has been achieved via exfoliation of bulk carbon nitride using supercritical CO2 . The resultant hybrid structure, CNNS/MFM-300(Fe), comprising carbon nitride nanosheets (CNNS) and MFM-300(Fe), shows excellent performance towards photocatalytic aerobic oxidation of benzylic C–H groups at room temperature under visible light. The catalytic activity is significantly improved compared to the parent g-C3 N4, MFM-300(Fe) or physical mixtures of both. This facile strategy for preparing heterojunction photocatalysts demonstrates a green pathway for the efficient and economic oxidation of benzylic carbons to produce fine chemicals.